Factors Influencing Marital Satisfaction among Couples as Perceived by Counsellors in Ilorin Metropolis - Adebayo, David Obafemi (Buletin Konseling Inovatif, 2025)
The study investigated the factors influencing marital satisfaction among couples as perceived by counsellors in Ilorin metropolis, Kwara State. The objectives of the study were to examine various factors that could influence the individual couple satisfaction in marriage. The study was guided by one research question which was raised and answered and it employed the descriptive design, a population simple random sampling technique was use to select a total of one hundred and fifty (150) married adult within Ilorin metropolis Area of Kwara State. The data collected through the administered questionnaire was subjected to descriptive statistics; frequency count, simple percentage, mean and standard deviation while hypotheses was analysis using Analysis of Variance (ANOVA). The findings from the analysis revealed that; there is no significant difference in the factor influencing marital satisfaction among couples as perceived by counsellors in Ilorin metropolis based on gender, highest educational background, religion, years of counselling experience and marital status. Thus, based on the findings it was recommended that married people should find ways of improving in the level of intimacy in their marital relationship. Also, there should be heighten the level of their sexual experiences in order to improve the level of their marital satisfaction and there is need for proper understanding of one selves and good communication pattern, tolerance and mind of forgiveness to live happily.